PENGUJIAN CHARGER MODUL SIMULASI SOLAR CELL UNTUK MENYUPLAI WARNING LIGHT - Teresna, I Wayan; Sugiarta, I Nym; Suparta, I Nengah (BULETIN FISIKA; Vol 15 No 2 (2014): BULETIN FISIKA, 2014)
Simulation Module Testing Solar Cell Charger For Supplies the Warning Light Simulation module has been tested solar cell charger to supply the battery warning light on two different, where the purpose of the author can test solar cell circuit simulation for supply warning light, to save / power supply / energy resources considering the energy resources in our country on the wane, the government is planning to wear solar energy. Thus the authors tried to make a series of simulation testing of the solar cell to supply warning light And there was its function is to determine its capacity tool / charger module simulation of solar cells and battery / batteries are different still feasible or optimal used to supply warning light. The lamp warning light works on voltage DC (Direct Current) which absorbed sunlight the solar cell module is converted into DC voltage. Module testing solar cells as an energy source electricity were, for the storage of electrical energy in the battery as a source of energy that will turn on the lights for warning light for 24 hours. Simulation modules use solar cells to DC LED warning light using very precisely applied is by using solar power, so we can save on electricity costs due to the LED DC can not dole directly from PLN net. In this paper the authors perform Simulation Testing of Solar Cell Charger Module to supply warning light and analysis for the selection of solar cell capacity, and the capacity of the battery / batteries are different.